The role of playing in psyche development: understanding in light of cultural-historic outlook (Research, Society and Development, 2022)
This study had as objective to understand the role of playing during child psyche development process in pre-school period from pre-school teachers’ perspective and in light of theorical suppositions of historic-cultural outlook. It is an exploratory research with qualitative approach, which involved 60 teachers who answered a questionnaire about psyche development and the role of playing during pre-school period, which was carried out via Google Forms. The answers were organized by discursive textual analyses emerging therefore two categories: a) interaction and b) appropriation. Results disclose that psyche as a cross-functional system is developed by children interaction with their context, and in pre-school period is via playing that they feel suited to the world. It is important to note that, during this period of the child’s life, plays are instruments of learning facilitation in school and need to be explored by teachers pedagogically-oriented.